Evolution of crushing process of coarse-grained soil filler under the trains load - Qiyun Wang; Jiajun Zeng; Qingqing Shen; Huaming Lin; Yao Long (Scientific Reports)
Abstract Research on the evolutionary behavior of the particle breakage processes in coarse-grained soil under the action of train load is of practical significance for subgrade construction and maintenance. However, existing studies have not addressed the prediction of particle size distribution evolution. In this paper, the MTS loading system is used to simulate the dynamic train load effect on coarse-grained soil fillers. The study analyzes the influence of dynamic stress amplitude, loading frequency, and vibration times on both the macro-characteristics and micro-characteristics of particle breakage. The characteristics of particle fragmentation in coarse soil filler under high-speed train load are elucidated. Furthermore, a predictive model for the evolution of particle size distribution curves in relation to particle content and relative particle size is established using the ZHU continuous grading curve equation. This model captures the evolution process of particle breakage characteristics in coarse-grained soil fillers subjected to high-speed train loads. The applicability of this model has been verified. Based on the grading prediction model, an integral expression for the breakage rate index is derived, and the evolution characteristics of particle breakage in coarse-grained soil fillers under the action of train load are analyzed. The results indicate that during filling, the particle breakage mode of coarse-grained soil fillers during filling is primarily characterized by fracture and fragmentation; conversely, under dynamic cyclic loading conditions, it is predominantly characterized by fracture and grinding. The breakage rate aligns with the measured results, suggesting that the breakage rate index established in this study can effectively describe the evolution process of particle breakage in railway subgrade coarse-grained soil. After the reaching one million loading cycles, both deformation and particle breakage degree in coarse-grained soil fillers tend to stabilize. Under the action of dynamic stress amplitudes ranging from 10 to 200 kPa and loading frequencies between 2 and 12 Hz, the particle breakage index stabilizes below 1.1%. These research findings contribute to a deeper understanding of the evolutionary processes affecting engineering characteristics of railway subgrade coarse-grained soils and provide a theoretical as well as experimental foundation for railway subgrade construction and maintenance.